Automated robotic systems in surgical practice - Aleksandr А. Andreev; Aleksandr A. Glukhov; Anton P. Ostroushko; Anastasiya Y. Laptieva; Dmitrii A. Bokov; Nikolai O. Mikhailov; Pavel A. Konovalov (Наука и инновации в медицине, 2024)
The use of robotic systems has long gone beyond experimental medicine. More than 200 thousand operations per year are carried out with the use of just the most popular robotic complex Da Vinci. Further development of robotics will contribute to improvement of quality and accuracy of surgical interventions. Even now, it enables reduction of postoperative complications to almost zero. This review presents the analysis of the results of introducing robots into surgery. An overview of the data presented in PubMed, Cochrane Library, Science Direct and eLIBRARY was performed.